Influence of processing and storage on the iodine content of meat and fish products using iodized salt. (30th September 2022) - Meinhardt, Ann-Katrin; Müller, Alexandra; Lohmayer, Regina; Dederer, Irina; Manthey-Karl, Monika; Münch, Siegfried; Brüggemann, Dagmar; Fritsche, Jan; Greiner, Ralf
Highlights: KIO3 addition increased the iodine content in fish and meat products. Iodine was quantified with ICP-MS after NH3 extraction. The iodine content remained mostly constant during the applied processes and storage. After heating of the ham batter cooking loss lead to lower iodine contents. Fermentation of salami lead to loss of water and iodine. Abstract: Table salt fortified with KIO3 is commonly used to prevent iodine deficiency disorders. However, there is a lack of reliable data about the stability of KIO3 during food processing. In this study several meat and fish products were prepared with iodized salt and the iodine stability was determined through the whole production process. Applied processes included heating, fermenting, freezing, hot smoking, ripening by enzymes and storing. In all products an increase in iodine content was observed after addition of iodized salt. The iodine content remained constant during most of the applied processes. The only iodine loss was observed in ham after heating and can be explained by loss of iodine containing brine. During subsequent storage no iodine loss was observed in any of the products. The use of KIO3 fortified salt in the investigated products might therefore be beneficial for the iodine supply.